Diaphragm and preparation method thereof, electrochemical device and electronic device

CN119256443APending Publication Date: 2025-01-03NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280096233.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-05-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing secondary battery separators have poor thermal stability in high-temperature environments or thermal runaway caused by short circuits or overcharging, and are prone to uneven shrinkage or membrane rupture, affecting safety performance and cycle life.

Method used

A cellulose composite separator is used, including a polyethylene or polypropylene substrate and a microcrystalline cellulose layer and microcrystalline cellulose in the pores. The microcrystalline cellulose layer is formed through surface modification treatment and induced deposition, and the thickness and porosity are controlled to Improve thermal stability and electrolyte wettability.

Benefits of technology

It improves the safety performance, rate performance and cycle life of the electrochemical device, reduces the risk of thermal runaway, and optimizes the ion transport capability of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256443A_ABST
    Figure CN119256443A_ABST
Patent Text Reader

Abstract

According to the diaphragm and the preparation method thereof, the electrochemical device and the electronic device, the cellulose composite diaphragm comprises a base material, a microcrystalline cellulose layer located on at least one surface of the base material and microcrystalline cellulose located in pores of the base material, and the base material comprises polyethylene and / or polypropylene. In the cellulose composite diaphragm, the base material comprises polyethylene and / or polypropylene, the cellulose composite diaphragm simultaneously comprises microcrystalline cellulose (microcrystalline cellulose layers and microcrystalline cellulose in base material pores), and polyethylene and / or polypropylene and microcrystalline cellulose can play a synergistic effect; therefore, the cellulose composite diaphragm has good thermal stability, electrolyte wettability and high-temperature hole closing characteristic. Therefore, the electrochemical device applying the cellulose composite diaphragm disclosed by the invention can have good safety performance, rate capability and relatively long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Diaphragm and preparation method thereof, electrochemical device and electronic device Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a diaphragm and a preparation method thereof, an electrochemical device, and an electronic device. Background Art

[0002] Secondary batteries, with their high specific energy, high operating voltage, low self-discharge rate, compact size, and light weight, are widely used in various fields, including energy storage, portable electronic devices, and electric vehicles. With the rapid development of electric vehicles and portable electronic devices, people's demand for the performance of secondary batteries is also increasing.

[0003] The commonly used separators in secondary batteries are polyethylene (PE) or polypropylene (PP) separators, but the above separators have the problem of poor thermal stability. That is, when the secondary battery is in a high ambient temperature, or when it generates heat due to short circuit, overcharge, etc., the separator is prone to uneven shrinkage and rupture, and then internal short circuit and thermal runaway occur. At the same time, PP or PE separators have poor wettability and liquid retention in electrolytes, which has an adverse effect on the safety performance, rate performance and cycle life of secondary batteries.

[0004] Summary of the Invention

[0005] The present application provides a diaphragm and a preparation method thereof, an electrochemical device, and an electronic device to improve the safety performance, rate performance, and cycle life of the electrochemical device.

[0006] It should be noted that, in the invention content of the present application, the present application is explained by taking a lithium-ion battery as an example of an electrochemical device, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0007] The first aspect of the present application provides a cellulose composite membrane, which includes a substrate and a microcrystalline cellulose layer located on at least one surface of the substrate and microcrystalline cellulose located in the pores of the substrate, wherein the substrate includes polyethylene and / or polypropylene. In the cellulose composite membrane, the substrate includes polyethylene and / or polypropylene, and the cellulose composite membrane also includes microcrystalline cellulose (microcrystalline cellulose layer and microcrystalline cellulose in the pores of the substrate), polyethylene and / or polypropylene and microcrystalline cellulose can play a synergistic role, so that the cellulose composite membrane has good thermal stability, electrolyte wettability and high-temperature closed-pore characteristics. Thus, the electrochemical device using the cellulose composite membrane of the present application can have good safety performance, rate performance and long cycle life.

[0008] In one embodiment of the present application, the thickness of the microcrystalline cellulose layer is 2 μm to 20 μm, and the thickness of the substrate is 4 μm to 30 μm. Controlling the thickness of the microcrystalline cellulose layer and the thickness of the substrate within the above ranges is more conducive to improving the safety performance, rate capability, and energy density of the electrochemical device, and extending the cycle life of the electrochemical device.

[0009] In one embodiment of the present application, the porosity of the cellulose composite membrane is 40% to 70%. In another embodiment of the present application, the porosity of the cellulose composite membrane is 45% to 60%. Controlling the porosity of the cellulose composite membrane within the above range can provide the cellulose composite membrane with excellent ion transport capacity and strength, thereby further improving the rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0010] In one embodiment of the present application, the thermal shrinkage of the cellulose composite separator after heating at 120°C for 1 hour is 0% to 1.0%. In another embodiment of the present application, the thermal shrinkage of the cellulose composite separator after heating at 120°C for 1 hour is 0.2% to 0.8%. In yet another embodiment of the present application, the thermal shrinkage of the cellulose composite separator after heating at 120°C for 1 hour is 0.4% to 0.6%. This indicates that the thermal shrinkage of the cellulose composite separator after heating at 120°C for 1 hour is low, and the cellulose composite separator has good thermal stability. This is further conducive to improving the safety performance of the electrochemical device.

[0011] In one embodiment of the present application, the liquid absorption rate of the cellulose composite membrane is 100% to 240%. In another embodiment of the present application, the liquid absorption rate of the cellulose composite membrane is 120% to 200%. In yet another embodiment of the present application, the liquid absorption rate of the cellulose composite membrane is 140% to 180%. Controlling the liquid absorption rate of the cellulose composite membrane within the above range is more conducive to improving the safety performance and rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0012] A second aspect of the present application provides a method for preparing a cellulose composite separator, which comprises the following steps:

[0013] (1) Surface modification of the substrate in air or oxygen atmosphere;

[0014] (2) placing the substrate in a microcrystalline cellulose dispersion, independently inducing deposition to form microcrystalline cellulose layers on both surfaces of the substrate, and forming microcrystalline cellulose located in the pores of the substrate; or

[0015] (2′) coating the microcrystalline cellulose dispersion on the first surface of the substrate to form a microcrystalline cellulose layer on the first surface of the substrate and to form microcrystalline cellulose located in the pores of the substrate;

[0016] (3) washing with water and vacuum drying to obtain the cellulose composite separator described in any of the above schemes;

[0017] Wherein, the substrate comprises polyethylene and / or polypropylene.

[0018] The preparation method of the cellulose composite diaphragm of the present application is simple and easy to operate and can be widely used in industrial production. In the cellulose composite diaphragm prepared by the preparation method of the present application, polyethylene and / or polypropylene and microcrystalline cellulose can play a synergistic role, so that the cellulose composite diaphragm has good thermal stability, electrolyte wettability and high-temperature closed-pore properties. As a result, the electrochemical device using the cellulose composite diaphragm of the present application can have good safety performance, rate performance and long cycle life.

[0019] In one embodiment of the present application, in step (2), the induced deposition temperature is 0°C to 60°C, and the deposition time is 10 min to 360 min. Regulating the deposition temperature and deposition time within the above ranges is more conducive to destroying the hydrogen bonds formed between the microcrystalline cellulose and the microcrystalline cellulose dispersion, inducing the microcrystalline cellulose to precipitate and deposit on the substrate, and preparing a cellulose composite membrane comprising a substrate, microcrystalline cellulose layers on both surfaces of the substrate, and microcrystalline cellulose located in the pores of the substrate, thereby further improving the safety performance and rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0020] In one embodiment of the present application, the microcrystalline cellulose dispersion comprises NaOH, urea, microcrystalline cellulose, and water, wherein the mass percentage of the microcrystalline cellulose is 1% to 4% based on the mass of the microcrystalline cellulose dispersion. Controlling the mass percentage of the microcrystalline cellulose within the above range facilitates the formation of a microcrystalline cellulose layer, thereby improving the safety and rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0021] A third aspect of the present application provides an electrochemical device, which includes the cellulose composite diaphragm described in any of the aforementioned schemes; or, includes the cellulose composite diaphragm prepared by the preparation method described in any of the aforementioned schemes.

[0022] A fourth aspect of the present application provides an electronic device comprising the electrochemical device described in any of the aforementioned schemes.

[0023] Beneficial effects of this application:

[0024] The present application provides a diaphragm and its preparation method, electrochemical device and electronic device, wherein the polyethylene and / or polypropylene in the cellulose composite diaphragm and the microcrystalline cellulose can play a synergistic role, so that the cellulose composite diaphragm has good thermal stability, electrolyte wettability and high-temperature closed-pore properties. In this way, when the cellulose composite diaphragm of the present application is applied to the electrochemical device, when the electrochemical device is in a high-temperature environment or when it is self-heated due to short circuit, overcharging, etc., the good thermal stability of the cellulose composite diaphragm can reduce the risk of uneven shrinkage or membrane rupture; when the internal temperature of the electrochemical device rises to above 130°C, the cellulose composite diaphragm will exert its good high-temperature closed-pore properties, promptly cut off the internal current channel of the electrochemical device, and further reduce the risk of thermal runaway of the electrochemical device; the good electrolyte wettability of the cellulose composite diaphragm can effectively adjust the internal resistance of the electrochemical device, improve the rate performance of the electrochemical device, and extend the cycle life of the electrochemical device. As a result, the electrochemical device using the cellulose composite diaphragm of the present application can have good safety performance, rate performance and a long cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other drawings based on these drawings.

[0026] FIG1 is a schematic diagram of a preparation process of a cellulose composite separator according to an embodiment of the present application;

[0027] FIG2 is a schematic diagram of a preparation process of a cellulose composite separator according to another embodiment of the present application.

[0028] Description of reference numerals:

[0029] 10 substrate; 20 active site; 30 microcrystalline cellulose layer; 31 microcrystalline cellulose; 101 first surface; 102 second surface. DETAILED DESCRIPTION

[0030] To make the objectives, technical solutions, and advantages of this application more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and examples. It is apparent that the described examples are only a portion of the embodiments of this application, and not all of them. All other embodiments derived by persons of ordinary skill in the art based on the examples in this application are intended to fall within the scope of protection of this application.

[0031] It should be noted that, in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.

[0032] In a first aspect, the present application provides a cellulose composite separator comprising a substrate, a microcrystalline cellulose layer located on at least one surface of the substrate, and microcrystalline cellulose located in the pores of the substrate, wherein the substrate comprises polyethylene and / or polypropylene. In the cellulose composite separator, the substrate comprises polyethylene and / or polypropylene, and the cellulose composite separator also comprises microcrystalline cellulose (microcrystalline cellulose layer and microcrystalline cellulose in the pores of the substrate), and the polyethylene and / or polypropylene and the microcrystalline cellulose can play a synergistic role, so that the cellulose composite separator has good thermal stability, electrolyte wettability and high-temperature closed-pore properties. In this way, when the cellulose composite diaphragm of the present application is applied to an electrochemical device, when the electrochemical device is in a high temperature environment, or when it is self-heated due to short circuit, overcharging, etc., the good thermal stability of the cellulose composite diaphragm can reduce the risk of uneven shrinkage or membrane rupture; when the internal temperature of the electrochemical device rises to above 130°C, the cellulose composite diaphragm will exert its good high-temperature closed-pore properties, promptly cut off the internal current channel of the electrochemical device, and further reduce the risk of thermal runaway of the electrochemical device; the good electrolyte wettability of the cellulose composite diaphragm can effectively adjust the internal resistance of the electrochemical device, improve the rate performance of the electrochemical device, and extend the cycle life of the electrochemical device. As a result, the electrochemical device using the cellulose composite diaphragm of the present application can have good safety performance, rate performance and a long cycle life.

[0033] In the present application, the above-mentioned “microcrystalline cellulose layer located on at least one surface of the substrate” can be understood as the microcrystalline cellulose layer being located on both surfaces of the substrate, or on either surface of the two surfaces of the substrate. For example, (c) in FIG1 shows a schematic diagram of the cross-sectional structure of a cellulose composite membrane in one embodiment of the present application. As shown in (c) in FIG1 , the cellulose composite membrane comprises a substrate 10 and microcrystalline cellulose layers 30 located on both surfaces of the substrate 10 and microcrystalline cellulose 31 located in the pores (not shown) of the substrate 10. (f) in FIG2 shows a schematic diagram of the cross-sectional structure of a cellulose composite membrane in another embodiment of the present application. As shown in (f) in FIG2 , the cellulose composite membrane comprises a substrate 10 and a microcrystalline cellulose layer 30 located on the first surface 101 of the substrate 10 and microcrystalline cellulose 31 located in the pores (not shown) of the substrate 10. Of course, the microcrystalline cellulose layer 30 may also be located on the second surface 102 of the substrate 10.

[0034] In one embodiment of the present application, referring to FIG1( c ), the thickness Y of the microcrystalline cellulose layer 30 is 2 μm to 20 μm, and the thickness X of the substrate 10 is 4 μm to 30 μm. For example, the thickness Y of the microcrystalline cellulose layer 30 may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 13 μm, 16 μm, 20 μm, or any value between any two of the above numerical ranges. The thickness X of the substrate layer 10 may be 4 μm, 8 μm, 12 μm, 16 μm, 20 μm, 25 μm, 30 μm, or any value between any two of the above numerical ranges. If the thickness Y of the microcrystalline cellulose layer 30 and the thickness X of the substrate 10 are too thin (for example, Y is less than 2 μm and X is less than 4 μm), the thermal stability, electrolyte wettability and high-temperature closed-pore characteristics of the cellulose composite separator will be affected, thereby affecting the safety performance, rate performance and cycle life of the electrochemical device. If the thickness Y of the microcrystalline cellulose layer 30 and the thickness X of the substrate 10 are too thick (for example, Y is greater than 20 μm and X is greater than 30 μm), the internal ion transmission path of the electrochemical device will increase, the internal resistance will increase, which will affect the rate performance of the electrochemical device, and the volume of the electrochemical device will increase accordingly, which will affect the volume energy density of the electrochemical device. Regulating the thickness Y of the microcrystalline cellulose layer 30 and the thickness X of the substrate 10 within the above range is more conducive to improving the safety performance, rate performance, energy density of the electrochemical device and extending the cycle life of the electrochemical device. It should be noted that in this application, the thickness Y of the microcrystalline cellulose layer refers to the thickness of a single layer of microcrystalline cellulose layer located on one surface of the substrate layer.

[0035] In one embodiment of the present application, the porosity α of the cellulose composite diaphragm is 40% to 70%. In another embodiment of the present application, the porosity of the cellulose composite diaphragm is 45% to 60%. For example, the porosity α of the cellulose composite diaphragm can be 40%, 45%, 50%, 55%, 60%, 65%, 70% or any value between any two of the above numerical ranges. If the porosity α of the cellulose composite diaphragm is too low (for example, less than 40%), the electrolyte will have difficulty in infiltrating the cellulose composite diaphragm, affecting the ion transmission capacity of the cellulose composite diaphragm and increasing the internal resistance of the electrochemical device; if the porosity α of the cellulose composite diaphragm is too high (for example, greater than 70%), the cellulose composite diaphragm becomes loose and the strength decreases, affecting the puncture resistance of the cellulose composite diaphragm. By regulating the porosity α of the cellulose composite diaphragm within the above range, the cellulose composite diaphragm can have excellent ion transmission capacity and strength, which is more conducive to improving the rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0036] In one embodiment of the present application, the thermal shrinkage of the cellulose composite membrane when heated at 120°C for 1 hour is 0% to 1.0%. In another embodiment of the present application, the thermal shrinkage of the cellulose composite membrane when heated at 120°C for 1 hour is 0.2% to 0.8%. In yet another embodiment of the present application, the thermal shrinkage of the cellulose composite membrane when heated at 120°C for 1 hour is 0.4% to 0.6%. For example, the thermal shrinkage of the cellulose composite membrane when heated at 120°C for 1 hour can be 0%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0% or any value between any two of the above numerical ranges. This shows that the thermal shrinkage of the cellulose composite membrane when heated at 120°C for 1 hour is low, and the cellulose composite membrane has good thermal stability, which is more conducive to improving the safety performance of the electrochemical device.

[0037] In one embodiment of the present application, the liquid absorption rate of the cellulose composite membrane is 100% to 240%. In another embodiment of the present application, the liquid absorption rate of the cellulose composite membrane is 120% to 200%. In yet another embodiment of the present application, the liquid absorption rate of the cellulose composite membrane is 140% to 180%. For example, the liquid absorption rate of the cellulose composite membrane can be 100%, 120%, 140%, 160%, 180%, 200%, 220%, 240% or any value between any two of the above numerical ranges. If the liquid absorption rate of the cellulose composite membrane is too low (for example, less than 100%), the electrolyte wettability and liquid retention of the cellulose composite membrane will decrease, which will affect the ion transmission ability of the cellulose composite membrane and increase the internal resistance of the electrochemical device; if the liquid absorption rate of the cellulose composite membrane is too high (for example, greater than 240%), the thickness of the cellulose composite membrane will increase and the ion transmission path will become longer. Controlling the liquid absorption rate of the cellulose composite diaphragm within the above range is more conducive to improving the safety performance and rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0038] A second aspect of the present application provides a method for preparing a cellulose composite separator, which comprises the following steps:

[0039] (1) Surface modification of the substrate in air or oxygen atmosphere;

[0040] (2) placing a substrate in a microcrystalline cellulose dispersion, independently inducing deposition to form microcrystalline cellulose layers on both surfaces of the substrate, and forming microcrystalline cellulose located in the pores of the substrate; or

[0041] (2′) applying the microcrystalline cellulose dispersion to the first surface of the substrate and filtering the dispersion to form a microcrystalline cellulose layer on the first surface of the substrate and forming microcrystalline cellulose located in the pores of the substrate;

[0042] (3) washing with water and vacuum drying to obtain the cellulose composite separator described in any of the above schemes;

[0043] Wherein, the substrate comprises polyethylene and / or polypropylene.

[0044] The preparation method of the cellulose composite diaphragm of the present application is simple and easy to operate and can be widely used in industrial production. In the cellulose composite diaphragm prepared by the preparation method of the present application, polyethylene and / or polypropylene and microcrystalline cellulose can play a synergistic role, so that the cellulose composite diaphragm has good thermal stability, electrolyte wettability and high-temperature closed-pore properties. As a result, the electrochemical device using the cellulose composite diaphragm of the present application can have good safety performance, rate performance and long cycle life.

[0045] In the present application, there is no particular limitation on the method of surface modification of the substrate in the above-mentioned step (1), as long as the purpose of the present application can be achieved. For example, the substrate can be surface modified by a microwave plasma treatment method. There are no particular limitations on the parameters during microwave plasma treatment, as long as the purpose of the present application can be achieved. For example, the power is 2KW to 6KW, the voltage is 100V to 300V, and the time is 40s to 120s. By surface modification of the substrate, polar oxygen-containing groups such as COO-, C=O, and COC will be introduced into the surface of the substrate and the surface of the substrate pores after the surface modification treatment to form polar sites, so as to facilitate the attachment of microcrystalline cellulose to the substrate in step (2) or step (2'), and further form a microcrystalline cellulose layer and microcrystalline cellulose located in the pores of the substrate.

[0046] For example, FIG1 shows a schematic diagram of the preparation process of a cellulose composite diaphragm according to an embodiment of the present application. As shown in FIG1 , the substrate 10 shown in (a) of FIG1 is subjected to surface modification treatment in an air or oxygen atmosphere according to the method of step (1), so that the surface of the substrate 10 and the surface of the substrate pores are increased with polar sites 20 as shown in (b) of FIG1 . Then, according to the method of step (2), the substrate 10 shown in (b) of FIG1 (containing polar sites 20) is placed in a microcrystalline cellulose dispersion, and the microcrystalline cellulose layer 30 shown in (c) of FIG1 is formed independently on the two surfaces of the substrate 10 by induced deposition, and microcrystalline cellulose 31 is formed in the pores of the substrate 10 (not shown). Finally, according to the method of step (3), the composite material in FIG1 (c) is washed with water and vacuum dried to obtain the cellulose composite diaphragm described in any of the aforementioned schemes.

[0047] Figure 2 shows a schematic diagram of the preparation process of a cellulose composite diaphragm according to another embodiment of the present application. As shown in Figure 2, the substrate 10 shown in (d) of Figure 2 is subjected to surface modification treatment in air or oxygen atmosphere according to the method of step (1), so that the polar sites 20 shown in (e) of Figure 2 are added to the surface of the substrate 10 and the surface of the substrate pores. Then, according to the method of step (2'), the microcrystalline cellulose dispersion is coated on the first surface 101 of the substrate 10 (containing polar sites 20) shown in (e) of Figure 2, and the microcrystalline cellulose layer 30 shown in (f) of Figure 2 is formed on the first surface 101 of the substrate 10, and microcrystalline cellulose 31 is formed in the pores (not shown) of the substrate 10. Finally, according to the method of step (3), the composite material in Figure 2 (f) is washed with water and vacuum dried to obtain the cellulose composite diaphragm described in any of the above schemes. Of course, in step (2'), the microcrystalline cellulose dispersion can also be applied to the second surface 102 of the substrate 10 (containing polar sites 20) shown in (e) of Figure 2 to form a microcrystalline cellulose layer 30 on the second surface 102 of the substrate 10, and to form microcrystalline cellulose 31 located in the pores of the substrate 10. It is understood that in this application, the first surface and the second surface of the substrate can be understood as either surface of the two surfaces of the substrate, and the use of "first" and "second" is merely for convenience of expression and does not limit the two surfaces of the substrate.

[0048] In one embodiment of the present application, in step (2), the deposition temperature of the induced deposition is 0°C to 60°C, and the deposition time is 10 min to 360 min. Preferably, the deposition temperature is 25°C to 60°C, and the deposition time is 10 min to 30 min. For example, the deposition temperature can be 0°C, 10°C, 20°C, 25°C, 30°C, 40°C, 45°C, 50°C, 60°C, or any value between any two of the above numerical ranges. For example, the deposition time can be 10 min, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, 210 min, 240 min, 270 min, 300 min, 330 min, 360 min, or any value between any two of the above numerical ranges. A deposition temperature that is too low (e.g., below 0°C) or too high (e.g., above 60°C), a deposition time that is too short (e.g., shorter than 10 minutes) or too long (e.g., longer than 360 minutes) is not conducive to the deposition of the microcrystalline cellulose layer, and the thickness of the microcrystalline cellulose layer, the uniformity of deposition, and the porosity of the cellulose composite membrane will all be affected. Regulating the deposition temperature and deposition time within the above range is more conducive to destroying the hydrogen bonds formed between the microcrystalline cellulose and the microcrystalline cellulose dispersion, inducing the precipitation and deposition of the microcrystalline cellulose on the substrate, and preparing a cellulose composite membrane comprising a substrate, a microcrystalline cellulose layer on both surfaces of the substrate, and microcrystalline cellulose in the pores of the substrate, thereby being more conducive to improving the safety performance and rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0049] In one embodiment of the present application, the microcrystalline cellulose dispersion includes NaOH, urea, microcrystalline cellulose, and water, wherein the mass percentage of the microcrystalline cellulose is 1% to 4% based on the mass of the microcrystalline cellulose dispersion. For example, the mass percentage of the microcrystalline cellulose can be 1%, 2%, 3%, 4%, or any value between any two of the above ranges. Regulating the mass percentage of the microcrystalline cellulose within the above range is more conducive to the formation of the microcrystalline cellulose layer, thereby further improving the safety performance and rate performance of the electrochemical device and extending the cycle life of the electrochemical device.

[0050] The present application does not particularly limit the mass of NaOH and urea in the microcrystalline cellulose dispersion, as long as the purpose of the present application can be achieved. For example, based on the mass of the microcrystalline cellulose dispersion, the mass percentage of NaOH is 3% to 15%, and the mass percentage of urea is 5% to 20%.

[0051] In the present application, the microcrystalline cellulose in the composition of the microcrystalline cellulose dispersion is microcrystalline cellulose known in the art. This microcrystalline cellulose is a granular product of natural cellulose hydrolysis, and its main component is a linear polysaccharide substance linked by β-1,4-glucosidic bonds, with a particle size of 20 μm to 80 μm and a limiting degree of polymerization of 15 to 375. This microcrystalline cellulose can be obtained commercially.

[0052] The present application does not particularly limit the preparation method of the microcrystalline cellulose dispersion, as long as the purpose of the present application can be achieved. For example, the preparation of the microcrystalline cellulose dispersion includes the following steps: mixing 3wt% to 15wt% of NaOH, 5wt% to 20wt% of urea and water to obtain a solution, cooling the solution to -20°C to 0°C, adding 1wt% to 4wt% of microcrystalline cellulose, and stirring until a colorless and transparent solution is obtained. The above mass percentages are based on the total mass of the microcrystalline cellulose dispersion.

[0053] A third aspect of the present application provides an electrochemical device comprising the cellulose composite separator described in any of the preceding embodiments; or comprising a cellulose composite separator prepared by the preparation method described in any of the preceding embodiments. Therefore, the electrochemical device of the present application has excellent safety performance, rate capability, and a long cycle life.

[0054] The electrochemical device of the present application also includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and an outer packaging. The present application has no particular restrictions on the positive electrode sheet, negative electrode sheet, electrolyte, and outer packaging, and can be any known positive electrode sheet, negative electrode sheet, electrolyte, and outer packaging in the art, as long as the purpose of the present application can be achieved.

[0055] The cellulose composite diaphragm of the present application is located between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet and prevent internal short circuit of the electrochemical device, allowing electrolyte ions to pass freely and completing the electrochemical charge and discharge process.

[0056] The present application does not particularly limit the type of electrochemical device, which may include various devices that undergo electrochemical reactions. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion battery, a sodium ion battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.

[0057] The preparation process of an electrochemical device is well known to those skilled in the art and is not particularly limited in this application. For example, it may include, but is not limited to, the following steps: stacking the positive electrode sheet, the cellulose composite separator, and the negative electrode sheet in sequence, and performing winding, folding, and other operations as needed to obtain a wound electrode assembly, placing the electrode assembly in a packaging case, injecting an electrolyte into the packaging case, and sealing the case to obtain the electrochemical device; or stacking the positive electrode sheet, the cellulose composite separator, and the negative electrode sheet in sequence, and then securing the four corners of the entire stacked structure with tape to obtain a stacked electrode assembly, placing the electrode assembly in a packaging case, injecting an electrolyte into the packaging case, and sealing the case to obtain the electrochemical device. In addition, as needed, overcurrent protection components, guide plates, etc. may be placed in the packaging case to prevent pressure rise and overcharging and discharging within the electrochemical device.

[0058] A fourth aspect of the present application provides an electronic device comprising the electrochemical device described in any of the aforementioned solutions. Therefore, the electronic device of the present application has good safety performance, rate performance, and a long cycle life.

[0059] The electronic device of the present application is not particularly limited and can be any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-type computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, a power tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.

[0060] Example

[0061] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.

[0062] Test methods and equipment:

[0063] Test of thickness Y of microcrystalline cellulose layer:

[0064] Use a microcrystalline cellulose thickness gauge to measure the thickness Y of the microcrystalline cellulose layer. First, use a punching machine to punch out two 100 mm x 100 mm sheets of cellulose composite membrane. Then, use the microcrystalline cellulose thickness gauge to measure the thickness of each cellulose composite membrane at the four corners and the center. Obtain a total of 10 thickness readings and calculate the average value, T. The thickness of the microcrystalline cellulose layer, Y, = (Tx) / 2, where X is the substrate thickness.

[0065] Test of porosity α of cellulose composite membrane:

[0066] The porosity α of the cellulose composite membrane was measured using the gas displacement method: Porosity α = (V - V0) / V × 100%, where the pore volume is V - V0, where V0 is the true volume of the sample being measured and V is the total volume of the sample. The test equipment was a fully automatic true density tester (AccuPyc II 1340), and helium was used as the test gas.

[0067] Thermal shrinkage test:

[0068] Five samples measuring 30 mm x 30 mm or greater were taken from each of the separators of each Example and Comparative Example in both the transverse (TD) and longitudinal (MD) directions. The actual dimensions of the samples were measured. The samples were then sandwiched between two pieces of A4 paper. After the oven temperature stabilized, the samples were placed in an oven and heated at 120°C for 1 hour. The post-heating dimensions were measured and the shrinkage ratio (s) was calculated: Shrinkage ratio (s) = (L0 - L0) / L0 × 100%, where L0 is the initial length in the TD or MD direction, and L is the length after heating. The average of the thermal shrinkage values ​​of the five samples was the thermal shrinkage ratio.

[0069] Liquid absorption test:

[0070] Cut five 100 mm x 100 mm pieces of the separator from each Example and Comparative Example and weigh them. Immerse each separator in the electrolyte of the corresponding Example or Comparative Example for 10 minutes. Remove the sample, blot the surface electrolyte with filter paper, and weigh it again. Calculate the percentage increase in mass after immersion as the liquid absorption rate, a, where a = (W - W0) / W0 × 100%, where W0 is the initial mass of the separator sample and W is the mass of the separator sample after absorbing the electrolyte. The average of the liquid absorption rates of the five separators is the liquid absorption rate.

[0071] Overcharge safety performance test:

[0072] Five lithium-ion batteries from each example and comparative example were discharged at 0.2C to 3.0V at 25±3°C. They were then overcharged at 0.5C. Charging was stopped when the voltage reached 6V. The test concluded when the battery temperature returned to room temperature ±10°C. If no fire or explosion occurred, the battery was considered to have passed the test. The test results are expressed as a pass rate (n / m), where m is the total number of lithium-ion batteries tested and n is the number of batteries that passed the test.

[0073] Rate discharge performance test:

[0074] Five lithium-ion batteries from each example and comparative example were tested for discharge capacity after full charge at 25±3°C. The discharge rates were 0.2C, 0.5C, 1C, and 2C, respectively. The relative discharge capacity at each rate was calculated using the 0.2C discharge capacity as a benchmark. The average value of the five lithium-ion batteries was used as the measured value.

[0075] Cycle life test:

[0076] Five lithium-ion batteries from each example and comparative example were charged at 0.7C constant current to 4.4V at 25±3°C, then charged at 4.4V constant voltage to 0.05C, and then discharged at 0.5C constant current to 3.0V. This constituted one charge-discharge cycle, and the test was conducted according to the aforementioned charge-discharge cycle. The number of cycles required for the lithium-ion battery's capacity to decay to 80% of its original capacity was defined as the cycle life of the lithium-ion battery. The average value of the five lithium-ion batteries was taken as the measured value.

[0077] Example 1

[0078] <Preparation of Cellulose Composite Separator>

[0079] (1) A PE substrate with a thickness of X = 5 μm and a porosity of 37% was surface modified by microwave plasma treatment in an atmospheric air atmosphere; wherein the microwave plasma treatment power was 4 kW, the voltage was 200 V, and the time was 80 s.

[0080] (2) placing the substrate obtained in step (1) in a microcrystalline cellulose dispersion, and independently inducing deposition to form a microcrystalline cellulose layer with a thickness of Y = 2 μm and microcrystalline cellulose located in the pores of the substrate on both surfaces of the substrate; wherein,

[0081] The deposition temperature of the induced deposition was 25 °C and the deposition time was 10 min;

[0082] The microcrystalline cellulose dispersion comprises: 7 wt % of NaOH, 12 wt % of urea, 1.5 wt % of microcrystalline cellulose and 79.5 wt % of water. The temperature of the microcrystalline cellulose dispersion is -12°C.

[0083] (3) The composite material obtained in step (2) is washed with water and vacuum-dried to obtain a cellulose composite diaphragm.

[0084] <Preparation of positive electrode sheet>

[0085] The positive electrode active material LiCoO2, conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97.6:1.2:1.2. N-methylpyrrolidone (NMP) was then added as a solvent to prepare a positive electrode slurry with a solid content of 75 wt%, which was then stirred evenly. The positive electrode slurry was evenly coated on one surface of a 10 μm thick aluminum foil and dried at 90°C to obtain a positive electrode sheet with a positive electrode active material layer of 100 μm. The above steps were then repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. The positive electrode sheet was cold pressed and cut into sheets measuring 74 mm x 867 mm for later use.

[0086] <Preparation of negative electrode sheet>

[0087] The negative electrode active materials, artificial graphite, sodium carboxymethyl cellulose, and styrene-butadiene rubber, were mixed in a mass ratio of 97.7:1.1:1.2. Deionized water was then added as a solvent to prepare a negative electrode slurry with a solid content of 70 wt%. The mixture was stirred evenly and evenly coated on one surface of a 6 μm thick copper foil. The slurry was then dried at 110°C to obtain a negative electrode sheet with a single-sided negative electrode active material layer and a coating thickness of 150 μm. The above coating steps were then repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided negative electrode active material layer. The negative electrode sheet was cold pressed and cut into sheets measuring 76 mm x 851 mm for later use.

[0088] <Preparation of Electrolyte>

[0089] In a dry argon atmosphere, organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a mass ratio of 30:40:30. LiPF6 was then added to the organic solvents, dissolved, and mixed thoroughly to obtain an electrolyte solution. The molar concentration of LiPF6 in the electrolyte solution was 1.05 mol / L.

[0090] <Preparation of lithium-ion batteries>

[0091] The prepared positive electrode sheet, cellulose composite separator, and negative electrode sheet are stacked in order, with the cellulose composite separator positioned between the positive and negative electrodes to act as a separator. The electrode assembly is then wound to form an electrode assembly. The electrode assembly is then placed in an outer packaging, injected with the prepared electrolyte, and packaged. The lithium-ion battery is then produced through a series of processes, including formation, degassing, and trimming.

[0092] Example 2 to Example 14

[0093] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1. Specifically, as the mass percentage of microcrystalline cellulose increases, the mass percentage of water decreases accordingly, while the mass percentages of NaOH and urea remain unchanged, so that the sum of the masses of NaOH, urea, microcrystalline cellulose, and water is 100%.

[0094] Comparative Example 1

[0095] The process is the same as that of Example 1 except that a PE substrate with a thickness of X=5 μm and a porosity of 37% is selected as the separator to replace the microcrystalline cellulose separator.

[0096] The preparation parameters of each embodiment and comparative example are shown in Table 1, and the performance parameters are shown in Table 2.

[0097] Table 1

[0098]

[0099] Note: “\” in Table 1 indicates no corresponding parameter; Comparative Example 1 selected a PE substrate with a thickness of 5 μm and a porosity of 37% as the diaphragm.

[0100] Table 2

[0101]

[0102] Comparison of Examples 1 to 14 with Comparative Example 1 reveals that, compared to the separator of Comparative Example 1, the cellulose composite separator of the present application has a greater porosity, less transverse and longitudinal thermal shrinkage, and a higher liquid absorption rate. When the cellulose composite separator of the present application is applied to lithium-ion batteries, the lithium-ion batteries have a higher overcharge safety test pass rate and cycle life, and exhibit good discharge capacity. This indicates that the safety and rate performance of lithium-ion batteries employing the cellulose composite separator of the present application are improved, and the cycle life is extended.

[0103] The mass percentage of microcrystalline cellulose in a microcrystalline cellulose dispersion generally affects the safety, rate capability, and cycle life of a lithium-ion battery. As can be seen from Examples 1 to 3, lithium-ion batteries using microcrystalline cellulose with a mass percentage within the range of this application exhibit good safety and rate capabilities, as well as a longer cycle life.

[0104] When forming a microcrystalline cellulose layer on a substrate surface, the deposition time of the induced deposition generally affects the safety, rate performance, and cycle life of the lithium-ion battery. As can be seen from Examples 3 to 6 and 10, lithium-ion batteries using deposition times within the range of this application exhibit good safety and rate performance, as well as a longer cycle life.

[0105] When forming a microcrystalline cellulose layer on a substrate surface, the deposition temperature of the induced deposition generally affects the safety, rate performance, and cycle life of the lithium-ion battery. As can be seen from Examples 3, 7, and 10, lithium-ion batteries using a deposition temperature within the range of this application exhibit good safety and rate performance, as well as a long cycle life.

[0106] The composition of the substrate generally affects the safety, rate capability, and cycle life of lithium-ion batteries. As can be seen from Examples 3, 11, and 12, lithium-ion batteries using substrate compositions within the scope of this application exhibit good safety and rate capabilities, as well as a long cycle life.

[0107] The thickness of the substrate generally affects the safety, rate performance, and cycle life of lithium-ion batteries. As can be seen from Examples 3, 13, and 14, lithium-ion batteries using substrates with thicknesses within the range of this application exhibit good safety and rate performance, as well as a long cycle life.

[0108] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity from another, and do not necessarily require or imply any actual relationship or order between these entities. Moreover, the terms "include," "comprise," or any other variations thereof are intended to cover non-exclusive inclusion, such that an article or device comprising a list of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such article or device.

[0109] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A cellulose composite diaphragm, characterized in that: The invention comprises a substrate, a microcrystalline cellulose layer located on at least one surface of the substrate and microcrystalline cellulose located in pores of the substrate, wherein the substrate comprises polyethylene and / or polypropylene.

2. The cellulose composite separator according to claim 1, wherein The thickness of the microcrystalline cellulose layer is 2 μm to 20 μm, and the thickness of the substrate is 4 μm to 30 μm.

3. The cellulose composite separator according to claim 1, characterized in that The porosity of the cellulose composite separator is 40% to 70%.

4. The cellulose composite separator according to claim 3, characterized in that The porosity of the cellulose composite separator is 45% to 60%.

5. The cellulose composite separator according to claim 1, characterized in that The thermal shrinkage of the cellulose composite separator when heated at 120° C. for 1 hour is 0% to 1.0%.

6. The cellulose composite separator according to claim 5, characterized in that The thermal shrinkage of the cellulose composite separator when heated at 120° C. for 1 hour is 0.2% to 0.8%.

7. The cellulose composite separator according to claim 6, characterized in that The thermal shrinkage of the cellulose composite separator when heated at 120° C. for 1 hour is 0.4% to 0.6%.

8. The cellulose composite separator according to claim 1, characterized in that The liquid absorption rate of the cellulose composite separator is 100% to 240%.

9. The cellulose composite separator according to claim 8, characterized in that The liquid absorption rate of the cellulose composite separator is 120% to 200%.

10. The cellulose composite separator according to claim 9, characterized in that The liquid absorption rate of the cellulose composite separator is 140% to 180%.

11. A method for preparing a cellulose composite diaphragm, characterized in that: The following steps are involved: (1) Surface modification of the substrate in air or oxygen atmosphere; (2) placing the substrate in a microcrystalline cellulose dispersion, independently inducing deposition to form microcrystalline cellulose layers on both surfaces of the substrate, and forming microcrystalline cellulose located in the pores of the substrate; or, (2′) coating the microcrystalline cellulose dispersion on the first surface of the substrate to form a microcrystalline cellulose layer on the first surface of the substrate and to form microcrystalline cellulose located in the pores of the substrate; (3) washing with water and vacuum drying to obtain the cellulose composite separator according to any one of claims 1 to 10; Wherein, the substrate comprises polyethylene and / or polypropylene.

12. The preparation method according to claim 11, characterized in that In step (2), the deposition temperature of the induced deposition is 0° C. to 60° C., and the deposition time is 10 min to 360 min.

13. The preparation method according to claim 11, characterized in that The microcrystalline cellulose dispersion comprises NaOH, urea, microcrystalline cellulose and water. Based on the mass of the microcrystalline cellulose dispersion, the mass percentage of the microcrystalline cellulose is 1% to 4%.

14. An electrochemical device, characterized in that A cellulose composite diaphragm comprising the cellulose composite diaphragm according to any one of claims 1 to 10; or a cellulose composite diaphragm prepared by the preparation method according to any one of claims 11 to 13.

15. An electronic device, characterized in that: An electrochemical device comprising the electrochemical device of claim 14.

Citation Information

Patent Citations

  • Porous inorganic coating / polyolefin microporous membrane compound diaphragm and preparation method thereof

    CN102977394A

  • High temperature-resistant composite diaphragm, and preparation method and application thereof

    CN108258171A

  • Separator, and separator for alkaline manganese dry battery comprising same

    CN111373570A

  • Method of manufacturing separator for battery and separator for battery

    JP2014096335A